Eddy Current Braking Experiment using Brake Disc from Aluminium Series of A16061 and A17075 - Mohamad Zairi, Baharom; M. Z., Nuawi; Priyandoko, Gigih; S. M., Harris (IOP Publishing, 2012)
The electromagnetic bra7ing using eddy current was studied, focused on two series of aluminium as the bra7e disc which are Al6061 and Al7075. This paper presents the comparison for both series in a few varied parameters related to eddy current bra7ing such as air-gap, number of turns and bra7e disc thickness. Optical tachometer has been used along with PULSE analyzer to capture the speed (rpm) and time (s). The findings shows that the smaller the air-gap, the larger of electromagnet turns and the thicker disc thickness.